ChemInform Abstract: Perovskite Solar Cells: Influence of Hole Transporting Materials on Power Conversion Efficiency. Issue 11 (February 2016) - Ameen, Sadia; Rub, Malik Abdul; Kosa, Samia A.; Alamry, Khalid A.; Akhtar, M. Shaheer; Shin, Hyung‐Shik; Seo, Hyung‐Kee; Asiri, Abdullah M.; Nazeeruddin, Mohammad Khaja
Abstract: Review: 89 refs.